2020
DOI: 10.1186/s12871-019-0922-4
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy and safety of peri-articular injection versus intra-articular injection in one-stage bilateral total knee arthroplasty: a randomized controlled trial

Abstract: Background: As an essential component of multimodal analgesia approaches after total knee arthroplasty (TKA), local infiltration analgesia (LIA) can be classified into peri-articular injection (PAI) and intra-articular injection (IAI) according to administration techniques. Currently, there is no definite answer to the optimal choice between the two techniques. Our study aims to investigate analgesic efficacy and safety of PAI versus IAI in patients receiving simultaneous bilateral TKA. Methods: This randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Cheng KY et al carried out a study during which they administered analgesic cocktails via periarticular injection to one knee and via intraarticular injection to the other knee of patients who underwent bilateral knee arthroplasty in the same session, thus conducting a randomized controlled study (15). In another study, the authors classi ed patients who underwent simultaneous bilateral knee arthroplasty into two groups, injected the PAI solution in a randomized manner to the rear or front compartments, and compared the pain and functional results (16).…”
Section: Discussionmentioning
confidence: 99%
“…Cheng KY et al carried out a study during which they administered analgesic cocktails via periarticular injection to one knee and via intraarticular injection to the other knee of patients who underwent bilateral knee arthroplasty in the same session, thus conducting a randomized controlled study (15). In another study, the authors classi ed patients who underwent simultaneous bilateral knee arthroplasty into two groups, injected the PAI solution in a randomized manner to the rear or front compartments, and compared the pain and functional results (16).…”
Section: Discussionmentioning
confidence: 99%
“…A sample size calculation 10 indicated that at least 32 patients would be needed in each group to detect a difference in morphine consumption of at least 2 mg with a power of 95% and type-I error of 5%, assuming that the standard deviation of the morphine consumption in each group would be 2 mg as in a previous study 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Adequate pain management following THA plays an important role in improving patients' overall satisfaction and enhancing functional recovery [ 1 , 2 ]. Multimodal analgesia for postoperative pain following THA has gained popularity, and one aspect of multimodal analgesia is local infiltration analgesia [ 3 5 ]. Administration techniques for local infiltration analgesia can be classified into periarticular injection (PAI) and intra-articular injection (IAI) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal analgesia for postoperative pain following THA has gained popularity, and one aspect of multimodal analgesia is local infiltration analgesia [ 3 5 ]. Administration techniques for local infiltration analgesia can be classified into periarticular injection (PAI) and intra-articular injection (IAI) [ 5 ]. Recently, we demonstrated that PAI containing triamcinolone acetonide had analgesic and anti-inflammatory effects following THA and had the potential to accelerate early ambulation and reduce the risk of deep vein thrombosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation